2000
DOI: 10.1021/ie000150i
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of Carbon Dioxide around Naphthalene Investigated using H/D Substitution in Neutron Diffraction

Abstract: The technique of hydrogen/deuterium substitution in neutron diffraction has been used to investigate the intermolecular structure of carbon dioxide saturated with naphthalene at supercritical pressure. The experiment was performed at P ) 206 bar and T ) 302 K, corresponding to a dilute concentration of approximately 1 C 10 H 8 molecule to 110 CO 2 molecules. Particular attention has been paid to the local structural environment of the hydrogen atoms through the extraction of the first-order neutron difference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
(38 reference statements)
0
8
1
Order By: Relevance
“…This is to be expected since the experimental pressure is approximately halfway between the two simulation pressures. Although an eight-membered ring of CO 2 molecules with molecular axes perpendicular to the plane of the naphthalene molecule (see Figure of ref ) was found to be consistent with the experimental scattering data, the orientation was based upon a gas-phase cluster calculation without temperature effects, that is, at 0 K 6 Structure factors for the systems containing N naph = 0 (upper) and 4 (lower) naphthalenes at T = 308.38 K and p = 87.8 (solid lines) and 310.2 bar (dotted lines).…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…This is to be expected since the experimental pressure is approximately halfway between the two simulation pressures. Although an eight-membered ring of CO 2 molecules with molecular axes perpendicular to the plane of the naphthalene molecule (see Figure of ref ) was found to be consistent with the experimental scattering data, the orientation was based upon a gas-phase cluster calculation without temperature effects, that is, at 0 K 6 Structure factors for the systems containing N naph = 0 (upper) and 4 (lower) naphthalenes at T = 308.38 K and p = 87.8 (solid lines) and 310.2 bar (dotted lines).…”
Section: Resultsmentioning
confidence: 63%
“…To improve SCF processes, it is of great technological importance to understand the microscopic details of the solvation mechanism of SCFs. Of great interest is whether the distribution of supercritical solvent molecules is relatively homogeneous on the microscopic scale or whether there is a pronounced clustering of solvent molecules around solutes. In a pioneering study, Eckert and co-workers experimentally measured the partial molar volume at infinite dilution of naphthalene, C 10 H 8 , dissolved in sc-CO 2 at temperatures of 308.38 and 318.15 K and pressures ranging from 74.6 to 373.0 bar . They reported large, negative partial molar volumes near the critical pressure, that is, the system volume decreases substantially upon addition of solute molecules.…”
Section: Introductionmentioning
confidence: 99%
“…13 compares the effect of size of the aromatic functional group on viscosity of CO 2 via contrast of the phenyl and naphthyl groups, where it is clear that the use of the single aromatic ring provides superior results. As noted above, this could be due to enhanced CO 2 aromatic interaction [43][44][45] or decreased aromatic-aromatic interaction due to bulkiness and close proximity of the rings to the backbone in the naphthyl case.…”
Section: Viscosity Behavior Results Of Copolymers In Dense Comentioning
confidence: 92%
“…Liquid ethanol, on the other hand, consists of shorter winding chains, each O–H group facing 1.8 nearest neighbors at an O–H···H bond distance of 2.8 Å . A combined neutron diffraction and molecular dynamic study showed, however, that a small fraction of the winding structures form clusters, e.g., hexamers and tetramers, by closing the loops of the winding chains. , In the TLFs of ethanol, the cluster formation may be easier due to the excess free energies associated with the ethanol molecules that cannot from O–H···H bonds with the confining surfaces. Another way to minimize free energy may be to locate the gauche rather than trans form of ethanol at the interface, as the former is the more stable form .…”
Section: Resultsmentioning
confidence: 99%